Shrubs Compensate for Tree Leaf Area Variation and Influence Vegetation Indices in Post‐Fire Siberian Larch Forests. Issue 3 (1st March 2023) - Bendavid, Nadav S.; Alexander, Heather D.; Davydov, Sergei P.; Kropp, Heather; Mack, Michelle C.; Natali, Susan M.; Spawn‐Lee, Seth A.; Zimov, Nikita S.; Loranty, Michael M.
Abstract: In post‐fire Siberian larch forests, where tree density can vary within a burn perimeter, shrubs constitute a substantial portion of the vegetation canopy. Leaf area index (LAI), defined as the one‐sided total green leaf area per unit ground surface area, is useful for characterizing variation in plant canopies. We estimated LAI with allometry for trees and tall shrubs (>0.5 and <1.5 m) across 26 sites with varying tree stem density (0.05–3.3 stems/m 2 ) and canopy cover (4.6%–76.9%) in a uniformly‐aged mature Siberian larch forest that regenerated following a fire ∼75 years ago. We investigated relationships between tree density, tree LAI, and tall shrub LAI, and between LAI and satellite observations of Normalized Difference and Enhanced Vegetation Indices (NDVI and EVI). Across the density gradient, tree LAI increases with increasing tree density, while tall shrub LAI decreases, exhibiting no patterns in combined tree‐shrub LAI. We also found significant positive relationships between tall shrub LAI and NDVI/EVI from PlanetScope and Landsat imagery. These findings suggest that tall shrubs compensate for lower tree LAI in tree canopy gaps, forming a canopy with contiguous combined tree‐shrub LAI across the density gradient. Our findings suggest that NDVI and EVI are more sensitive to variation in tall shrub canopies than variation in tree canopies or combined tree‐shrub canopies in these ecosystems. The results improve our understanding of the relationships between forest density and tree and shrub leaf area and have implications for interpreting spatial variability in LAI, NDVI, and EVI in Siberian boreal forests. Plain Language Summary: After wildfires burn forests in northeast Siberia, they often grow back unevenly, with some sections containing many more trees than others. Sections with more trees have a higher capacity to take up carbon and higher rates of energy production, which has important implications for climate change. To investigate how vegetation varies across sections of a forest which burned in 1940, we estimated the separate and combined contributions of trees and tall shrubs (>0.5 and <1.5 m) in high, medium, and low density sections using tree and shrub stem diameter measurements. We estimated the canopy vegetation in each section of forest by calculating the total area of leaves in the section and dividing it by the total ground area, producing the leaf area index (LAI). In sections with less dense tree cover, tall shrubs made up for lower tree leaf area, and the combined leaf area of trees and tall shrubs was consistent across the sections of different tree density. We also compared our leaf area measurements with measures of vegetation productivity produced from satellite imagery, finding that the satellite measures were correlated with tall shrub LAI, but not with tree LAI or combined LAI from trees and shrubs. Key Points: Tall shrubs compensate for lower tree leaf area in low density larch forests Combined leaf area of trees and tall shrubs is consistent across a range of forest tree densities Satellite‐derived v egetation indices are more closely linked to shrub LAI than tree LAI or combined tree‐shr LAI